ESTIMATION OF THE DECREASING OF 137 CS SEDIMENT IN THE SOIL DUE TO HORIZONTAL FLOWING - O. N. Prokof'ev (Радиационная гигиена)
The purpose of work is to estimate the possible decreasing of the density of  137 Cs sediment in the soil influenced by the horizontal flowing basing on the analysis of on location observations on the density of  137 Cs sediment in the soil after the Chernobyl accident.